2012
DOI: 10.4161/epi.19506
|View full text |Cite
|
Sign up to set email alerts
|

Smyd3 regulates cancer cell phenotypes and catalyzes histone H4 lysine 5 methylation

Abstract: Smyd3 is a lysine methyltransferase implicated in chromatin and cancer regulation. Here we show that Smyd3 catalyzes histone H4 methylation at lysine 5 (H4K5me). This novel histone methylation mark is detected in diverse cell types and its formation is attenuated by depletion of Smyd3 protein. Further, Smyd3-driven cancer cell phenotypes require its enzymatic activity. Thus, Smyd3, via H4K5 methylation, provides a potential new link between chromatin dynamics and neoplastic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
166
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(171 citation statements)
references
References 10 publications
5
166
0
Order By: Relevance
“…Similar results were observed upon depletion of the two homologous proteins, suv420h1/h2 in the zebrafish Danio rerio (23). There are reports of other KMTs such as NSD2/MMSET/WHSC1 having activity on H4K20 (24); however, careful analysis of NSD2-methylated histones demonstrated that this enzyme has absolutely no activity on H4K20 (25,26), and similar analyses have ruled out several other putative H4K20 methyltransferases (25)(26)(27)(28)(29). 2 Thus, in higher eukaryotes, SETD8 appears to be the sole monomethyltransferase for H4K20, and successive methylation of H4K20me1 by SUV4-20H1 and SUV4-20H2 generates the preponderance of global H4K20me2 and H4K20me3.…”
supporting
confidence: 57%
“…Similar results were observed upon depletion of the two homologous proteins, suv420h1/h2 in the zebrafish Danio rerio (23). There are reports of other KMTs such as NSD2/MMSET/WHSC1 having activity on H4K20 (24); however, careful analysis of NSD2-methylated histones demonstrated that this enzyme has absolutely no activity on H4K20 (25,26), and similar analyses have ruled out several other putative H4K20 methyltransferases (25)(26)(27)(28)(29). 2 Thus, in higher eukaryotes, SETD8 appears to be the sole monomethyltransferase for H4K20, and successive methylation of H4K20me1 by SUV4-20H1 and SUV4-20H2 generates the preponderance of global H4K20me2 and H4K20me3.…”
supporting
confidence: 57%
“…From these observations, it is possible that the H3K4me3 level depends on the type of methyltransferase and that SMYD3 modifies H3K4 within the promoter regions of the lineage-specific genes. In addition, a recent report demonstrated that although global levels of H3K4me3 do not change upon the loss of Smyd3 in the human breast carcinoma cell line, MCF7, the global levels of H4K5me, a novel chromatin target of Smyd3, do change (Van Aller et al 2012). This result indicates that SMYD3 is required for H4K5 methylation in cancer cells.…”
Section: Role Of Smyd3 In Embryonic Lineage Commitmentmentioning
confidence: 58%
“…SMYD3 methylates both H3K4 and H4K5 (Hamamoto et al 2004, Van Aller et al 2012, recruits RNA polymerase II through an RNA helicase to form a transcription complex, and elicits its oncogenic effects by activating the transcription of downstream target genes (Hamamoto et al 2004, 2006, Liu et al 2007. SMYD3 is also involved in apoptosis and the inhibition of cell growth, migration, and invasion (Xu et al 2006, Zou et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 However, recent studies have questioned this function and proposed H4K20 or H4K5 as SMYD3 substrates. 5,6 Indeed, SMYD3 knockdown led to global decreases in H4K5me without affecting total cellular H3K4 methylation levels. 6 However, it remains possible that specific localized events on selective promoters might contribute to SMYD3-driven tumorigenesis.…”
Section: Role Of the Smyd3 Histone Methyltransferase In Tumorigenesismentioning
confidence: 99%